2015
DOI: 10.1158/1078-0432.ccr-14-2022
|View full text |Cite|
|
Sign up to set email alerts
|

Pancreatic Cancer–Derived Exosomes Cause Paraneoplastic β-cell Dysfunction

Abstract: Background & Aims Pancreatic cancer (PC) frequently causes diabetes. We recently proposed adrenomedullin (AM) as a candidate mediator of pancreatic β-cell dysfunction in PC. How PC-derived AM reaches β-cells remote from the cancer to induce β-cell dysfunction is unknown. We tested a novel hypothesis that PC sheds AM-containing exosomes into circulation which are transported to β-cells and impair insulin secretion. Methods We characterized exosomes from conditioned media of PC-cell lines (n=5) and portal/peri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 37 publications
1
118
0
5
Order By: Relevance
“…Our group has previously shown that pancreatic tumors shed more exosomes than any other EV, and that these tumor-derived exosomes can mediate b-cell dysfunction and induce lipolysis in both in vitro and in vivo models of new-onset diabetes for PC. 8,9 This work suggests that tumorderived exosomes are mediators of paraneoplastic syndromes in PC. Therefore, we sought to examine the role of PC-derived exosomes (PC-Exo) in immunity for PC.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our group has previously shown that pancreatic tumors shed more exosomes than any other EV, and that these tumor-derived exosomes can mediate b-cell dysfunction and induce lipolysis in both in vitro and in vivo models of new-onset diabetes for PC. 8,9 This work suggests that tumorderived exosomes are mediators of paraneoplastic syndromes in PC. Therefore, we sought to examine the role of PC-derived exosomes (PC-Exo) in immunity for PC.…”
Section: Introductionmentioning
confidence: 81%
“…8,9 These important cellular cargos can aid in metabolic alterations that can help facilitate tumor growth. Exosomes have been strongly implicated in tumor immunity as mediators of both immune activation and suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Javeed et al showed that pancreatic cancer-derived exosomes, containing cancer antigen 19-9 (CA19-9) and Adrenomedullin (AM), which interacts adrenomedullin receptors (ADMRs) on β-cells, readily enter with β-cells via caveolin-mediated endocytosis or micropinocytosis. This exosomal uptake leads to the upregulation of endoplasmic reticular stress genes, such as Bip and Chop, which increases reactive oxygen/nitrogen species (ROS/RNS) production, resulting in failure of the unfolded protein response, inhibition of insulin secretion, and increased β-cell death [40]. Another study revealed a novel mechanism of exosome-induced lipolysis in pancreatic cancer.…”
Section: To Change the Metabolism Of Pancreatic Cancer Patientsmentioning
confidence: 99%
“…3 Compelling data also support the concept that pancreatic cancer itself can induce diabetes, which may precede the actual onset of pancreatic cancer symptoms by months. 4,5 The complexity of these relationships is outlined in Figure 1. Interestingly, antidiabetic therapy modulates the risk of developing pancreatic cancer; those treated with insulin or insulin secretagogues are at a higher risk, whereas patients treated with metformin have a significantly lower risk of pancreatic cancer.…”
Section: Relationship Between Diabetes and Pancreatic Cancermentioning
confidence: 99%